Thampramon tonvuthi, a new genus and new species of cavernicolous crab (Crustacea: Decapoda: Brachyura: Potamidae) from Thailand - Ng, Peter K. L.; Vidthayanon, Chavalit (Zootaxa, 2013)
A new genus and species of potamid cavernicolous crab, Thampramon tonvuthi sp. nov., is described from Thailand. While superficially similar to Tiwaripotamon Bott, 1970, Phaibulamon Ng, 1992, and Nemoron Ng, 1996, the new genus possesses a unique combination of morphological characters including a distinctive carapace form, possession of a rela-tively long third maxilliped exopod, long ambulatory legs and a unique male first gonopod.